Ionic‐Liquid‐Based Synthesis of the Germanium‐Iron Carbonyls FeI4GeI3Fe(CO)32 and (GeI3)2Fe(CO)4. Issue 1 (16th December 2016) - Wolf, Silke; Feldmann, Claus
Abstract : Dark red and brick red transparent crystals of FeI4 GeI3 Fe(CO)3 2 (1 ) and (GeI3 )2 Fe(CO)4 (2 ) were obtained by reacting GeI4 and Fe2 (CO)9 or Fe3 (CO)12 in a mixture of [BMIM]Cl and AlCl3 as ionic liquid (BMIm = 1‐butyl‐3‐methylimidazolium). According to X‐ray structure analysis based on single crystals, the title compounds exhibit cluster units with Fe–Ge bonds. FeI4 GeI3 Fe(CO)3 2 consists of two GeI2 I1/2 ‐Fe(CO)3 I2/2 units that are interlinked by a distorted octahedral FeI6/2 group. (GeI3 )2 Fe(CO)4 consists of two GeI3 units that are connected by a square planar Fe(CO)4 group with a linear Ge–Fe–Ge unit. Depending on the synthesis conditions, interestingly, (GeI3 )2 Fe(CO)4 crystallizes either in P 21 / n (2a ) or in P 1 (2b ).2a exhibits a more dense packing, whereas2b exhibits shorter intermolecular I–I distances. Both title compounds are temperature labile and highly sensitive to oxygen, moisture and illumination, including X‐ray irradiation. They decompose with release of CO in absence of certain CO atmosphere. In addition to crystal structure analysis the compounds were characterized by energy dispersive X‐ray (EDX) analysis, thermogravimetry (TG) and infrared spectroscopy (FT‐IR). Abstract :